2021
DOI: 10.1002/csc2.20466
|View full text |Cite
|
Sign up to set email alerts
|

Field resistance to wheat stem rust in durum wheat accessions deposited at the USDA National Small Grains Collection

Abstract: Wheat stem rust, caused by Puccinia graminis f. sp. tritici, is a re-emerging disease, posing a significant threat to durum wheat production worldwide. The limited number of stem rust resistance genes in modern cultivars compels us to identify and incorporate new effective genes in durum wheat breeding programs. We evaluated 8,245 spring durum wheat accessions deposited at the USDA National Small Grains Collection (NSGC) for resistance in field stem rust nurseries in Debre Zeit, Ethiopia and St. Paul, MN (USA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Recent studies have clearly demonstrated the potential of landraces to contribute diverse alleles for economic traits [ 32 , 33 , 34 , 35 , 36 , 37 ]. There are several examples of mining sources of resistance among the durum and tetraploid accessions in collections available in germplasm banks [ 6 , 33 , 34 , 35 , 36 , 38 , 39 , 40 , 41 , 42 , 43 ]. Mining these sources of resistance at times are very specific: for leaf rust as an example [ 6 , 38 , 41 ], yellow rust [ 39 , 40 , 43 ], stem rust [ 40 , 41 ], or other diseases [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have clearly demonstrated the potential of landraces to contribute diverse alleles for economic traits [ 32 , 33 , 34 , 35 , 36 , 37 ]. There are several examples of mining sources of resistance among the durum and tetraploid accessions in collections available in germplasm banks [ 6 , 33 , 34 , 35 , 36 , 38 , 39 , 40 , 41 , 42 , 43 ]. Mining these sources of resistance at times are very specific: for leaf rust as an example [ 6 , 38 , 41 ], yellow rust [ 39 , 40 , 43 ], stem rust [ 40 , 41 ], or other diseases [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several examples of mining sources of resistance among the durum and tetraploid accessions in collections available in germplasm banks [ 6 , 33 , 34 , 35 , 36 , 38 , 39 , 40 , 41 , 42 , 43 ]. Mining these sources of resistance at times are very specific: for leaf rust as an example [ 6 , 38 , 41 ], yellow rust [ 39 , 40 , 43 ], stem rust [ 40 , 41 ], or other diseases [ 37 ]. However, in only a few cases was resistance screening undertaken with the appropriate leaf rust races [ 25 , 38 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The higher proportion of susceptible lines against race JRCQC compared with race TKTTF (TKTTF_MS18) agrees with the findings of Hundie et al (2019) on evaluation of 14 durum wheat cultivars against four single races. Sr13a is moderately effective against JRCQC; however, the high frequency of susceptible lines to this race could also be explained by the reduced effect of this gene under field conditions (Olivera, et al, 2021), or the temperature dependence of Sr13 effectiveness as reported by Zhang et al (2017) in greenhouse evaluation of wheat lines, which may apply in the field because of the expected seasonal variation in temperature. The low frequency of resistant lines in TKTTF_MS19 was unusual, as durum wheat is known to have better resistance against race TKTTF.…”
Section: Field Response To Races Jrcqc and Tkttfmentioning
confidence: 95%
“…Recently, durum wheat accessions collections from around the world were tested for stem rust at hot spot locations, including here in Debre-zeit, Ethiopia, and Minnesota, USA. Surprisingly, the results showed that 98% of Ethiopian landraces were found to be resistant (Olivera et al, 2021). As a result, taking advantage of our natural resources is significantly better for the national breeding program for stem rust resistance.…”
Section: Correlations Between Stem Rust's Field Resistance Metricsmentioning
confidence: 98%